Estimating the impact of the Mongol expansion upon the gene pool of Tuvans - L. D. Damba; Е. V. Balanovskaya; M. K. Zhabagin; Y. М. Yusupov; Y. V. Bogunov; Z. M. Sabitov; A. T. Agdzhoyan; N. A. Korotkova; M. B. Lavryashina; B. B. Mongush; U. N. Kavai-ool; O. P. Balanovsky; et al. (Vavilov Journal of Genetics and Breeding, 2018)
With a view to trace the Mongol expansion in Tuvinian gene pool we studied two largest Tuvinian clans – those in which, according to data of humanities, one could expect the highest Central Asian ancestry, connected with the Mongol expansion. Thus, the results of Central Asian ancestry in these two clans component may be used as upper limit of the Mongol influence upon the Tuvinian gene pool in a whole. According to the data of 59 Y-chromosomal SNP markers, the haplogroup spectra in these Tuvinian tribal groups (Mongush, N = 64, and Oorzhak, N = 27) were similar. On average, two-thirds of their gene pools (63 %) are composed by North Eurasian haplogroups (N*, N1a2, N3a, Q) connected with autochtonous populations of modern area of Tuvans. The Central Asian haplogroups (C2, O2) composed less then fifth part (17 %) of gene pools of the clans studied. The opposite ratio was revealed in Mongols: there were 10 % North Eurasian haplogroups and 75 % Central Asian haplogroups in their gene pool. All the results derived – “genetic portraits”, the matrix of genetic distances, the dendrogram and the multidimensional scaling plot, which mirror the genetic connections between Tuvinian clans and populations of South Siberia and East Asia, demonstrated the prominent similarity of the Tuvinian gene pools with populations from and Khakassia and Altai. It could be therefore assumed that Tuvinian clans Mongush and Oorzhak originated from autochtonous people (supposedly, from the local Samoyed and Kets substrata). The minor component of Central Asian haplogroups in the gene pool of these clans allowed to suppose that Mongol expansion did not have a significant influence upon the Tuvinan gene pool at a whole. Для выявления следа монгольской экспансии в генофонде тувинцев впервые изучены генофонды двух самых многочисленных тувинских родов, для которых по данным гуманитарных наук ожидается наибольший вклад центральноазиатского компонента, связываемого с монгольской экспансией. При таком подходе результаты исследования могут ...